KONSEP BIMBINGAN DAN KONSELING ISLAM SOLUTION FOCUSED BRIEF THERAPY (SFBT) UNTUK MEMBANTU MENYEMBUHKAN PERILAKU PROKRASTINASI MAHASISWA - Frendi Fernando; Imas Kania Rahman (Fakultas Tarbiyah dan Keguruan UIN Ar-Raniry, 2016)
This article describes about concept of Islamic guidance and counseling through SFBT (Solution Focused Brief Therapy) approach to review helps cure procrastination student behavior. SFBT is a form of brief therapy that builds on the strengths of the counselee to help raise and construct a solution to the problem. The concept of guidance and counseling Islam through SFBT approach is a comprehensive approach so that more leverage in helping cure procrastination behavior. Procrastination is the tendency of delaying completion of a task or work related academic activities. Islamic SFBT its essence lies in the counseling phase focused on solutions rather than on problems so counselee more energy is used to find a solution. There are stages of intervention in the form of a question miracle (miracle question), the counselee is directed to find the magic solution that comes from Allah Swt. That with Allah, nothing is impossible if people want to try. Wisdom and the role of Allah Swt always